Chögyal Namkhai Norbu Rinpoche: Dzogchen and Tibetan Tradition. From Shang Shung to the West - Roberti di Sarsina, Paolo (Religions, 2012)
In July 2011 the International Dzogchen Community celebrated its 30th Anniversary. In 1981, near Arcidosso in Tuscany (Italy), Master Chögyal Namkhai Norbu Rinpoche founded the first community or Gar of the International Dzogchen Community. He named it “Meri-gar”, the “Community of the Mountain-of-Fire”. In the 70s Chögyal Namkhai Norbu began to teach Dzogchen to his first students. Interest soon became widespread and having received invitations from all continents, Chögyal Namkhai Norbu Rinpoche began to travel and teach throughout the world. These last thirty years the Dzogchen Community has grown and now has thousands of members in over 40 countries and all continents. The main objective of the Community is to preserve and develop understanding of Dzogchen, as well as preserving Tibet's extraordinary cultural patrimony. The International Shang Shung Institute for Tibetan Studies was founded by Chögyal Namkhai Norbu Rinpoche with this aim and it was inaugurated by His Holiness the 14th Dalai Lama in 1990. It has a rich collections of Tibetan books and manuscripts and publishes the teachings of Chögyal Namkhai Norbu. This article draws on Chögyal Namkhai Norbu’s work and legacy to describe the Dzogchen Lineage and Tibetan Tradition from the very origin of the Shang Shung Culture.